WISE mid-infrared properties of compact active galactic nuclei selected from the high radio frequency AT20G survey. Issue 1 (24th February 2020) - Chhetri, R; Kimball, A; Ekers, R D; Mahony, E K; Sadler, E M; Jarrett, T
ABSTRACT: Past studies of compact active galactic nuclei (AGNs), the dominant population at high radio frequencies, selected them using flat spectral index criteria. This biases the sample due to the steepening of AGN spectra at high radio frequencies. We improve upon this by selecting 3610 compact AGNs using their angular size information ( 0.15 arcsec scale) from the Australia Telescope 20 GHz (AT20G) high-angular resolution catalogue. We cross-match these against the Wide-field Infrared Survey Explorer AllWISE catalogue and present a catalogue with 3300 (91 per cent) matches, 91 (3 per cent) rejects, and 219 (6 per cent) non-detections that are excellent high-redshift candidates. Of the matched compact AGNs, 92 per cent exhibit QSO mid-infrared colours ( W 1− W 2 > 0.5). Therefore, our sample of high frequency compact sources has a very high rate of identification with mid-infrared QSOs. We find counterparts for 88 per cent of 387 compact steep-spectrum (CSS) sources in the AT20G survey, 82 ± 5 per cent of which exhibit QSO mid-infrared colours and have moderate redshifts ( z median = 0.82), while those dominated by host galaxy colours in mid-infrared have lower redshifts ( z median = 0.13). The latter classified into late- and early-type galaxies using their mid-infrared colours shows a majority (68 ± 4 per cent) have colours characteristic of late-type galaxies. Thus, we find that a larger fraction of these CSS sources are embedded in hosts with higher gas densities than average early-type galaxies. We compare mid-infrared colours of our AGNs against those reported for AGNs primarily selected using non-radio techniques. This shows that mid-infrared SED of high frequency selected compact radio AGN is comparatively less red, possibly due to contributions from their hosts.